Curative architecture, as a regeneration strategy for a vulnerable population with psychological problems - Pacheco Cabrera, Damar Elena; Vasquez Leiva, Keyli Gianella; Saldaña Fustamante, Eber Hernan (LACCEI, 2024)
The investigation is carried out based on the psychological problems that affect the inhabitants of Ayacucho, diseases that hinder the daily life of its citizens and the integral development of the city. Based on this, the research work addresses the objective of determining architectural design principles for a Center for the Treatment and prevention of psychological problems based on the principles of Stefan Lundin’s curative architecture in the province of Ayacucho 2023. The methodology used it is of a non-experimental type through documentary review; to be able to carry out, based on this, an architectural study in the selected environment, making use of different instruments. The result of the investigation resulted in both theoretical and technical guidelines, being applied through different types of enclosures in exterior spaces such as perimeter wall areas and interior spaces such as waiting rooms, workshops and main entrances, different types of scales such as double heights, employment of green areas between the different UPSS to generate visuals and direct connection with the outside, strategies for an adequate location, integrating the project with the environment.